Genetic Modulation of Coagulation Factor VII Plasma Levels: Contribution of Different Polymorphisms and Gender-related Effects - Castelnuovo, Augusto Di; D’Orazio, Andria; Amore, Concetta; Falanga, Anna; Kluft, Cornelis; Donati, Maria Benedetta; Iacoviello, Licia (Thrombosis and Haemostasis, 1998)
We studied the relationships among different polymorphisms of FVII gene in determining FVII levels, in a sample of 335 male and female Italian volunteers. The hypervariable region 4 (HVR4), the promoter decanucleotide insertion (-323 0/10 bp) and the R353Q polymorphisms of FVII gene were evaluated.The association of HVR4 or -323 0/10 bp polymorphism with plasma FVII levels differed between gender (Interaction term: p = 0.02 and p = 0.03, respectively), showing stronger effect in males than in females. In males, the R353Q and the HVR4 polymorphisms showed an incremental influence on FVII variance (F = 8.9, p < 0.001 and F = 4.4, p = 0.01, respectively). Moreover, the effects of Q and 10 bp alleles on the reduction of FVII activity levels were significantly potentiated by the presence of H7 allele of HVR4 (Interaction term p = 0.03 for R353Q*HVR4 and p = 0.03 for -323 0/10 bp*HVR4). In conclusion, the effect of FVII polymorphisms on FVII levels was gender dependent and derived from a complex interaction among them. The HVR4 polymorphism seems to add an independent, albeit small, contribution to the regulation of FVII plasma levels.